FUNCTIONAL CHARACTERIZATION AND PHYTOCHEMICAL PROFILING OF TERMINALIA CHEBULA FRUIT - Amina Jamil; Imran Pasha; Mian Kamran Sharif; Beenish Israr (Journal of Population Therapeutics and Clinical Pharmacology, 2023)
Terminalia chebula, one of the oldest plants cultivated on the earth, is rich in phytochemicals including phenolics, flavonoids, and organic acids. The present study was designed to analyze Terminalia chebula fruit and their extracts for nutritional composition and therapeutic potential. The proximate analysis indicated that 6.82±0.25%, 4.03±0.13%, 3.40±0.14%, 18.14±0.63%, 5.36±0.40%, 62.20±0.09% moisture, ash content, crude fat, crude fiber, crude protein and NFE, respectively present in Terminalia chebula fruit. The functional properties results revealed that pH of Terminalia chebula fruit was acidic and it exhibited the good swelling power, oil holding and water holding capacity. Terminalia chebula fruit was found to be rich in iron (815.33±10.33 ppm), zinc (33.66±0.3 ppm), manganese (33.81±0.41 ppm) and also have a good amount of copper, cobalt, calcium, magnesium, and potassium. The FTIR results have shown the presence of alcohol, alkane, aldehyde, thiol, amide and alkyl halide functional groups in chebulic fruit powder. Furthermore, the phytochemical and antioxidant properties of Terminalia chebula fruit by using different solvents (Methanol, ethanol and water) were measured and found that methanolic extract showed the higher TPC, TFC and radical scavenging properties.